Combining a Chest Wall Perforator Flap and Bioabsorbable Implant to Facilitate Oncoplastic Breast-conserving Surgery - Jean-Claude D. Schwartz, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Oncoplastic breast conservation is classically divided into two approaches: volume displacement and volume replacement (VR). These approaches are important to use when more than 20% of the breast is removed to avoid deformity. Smaller, nonptotic breasts require VR strategies from flaps based off of local chest wall perforators. When larger volumes are required, a flap based off the thoracodorsal artery can be used. Although this flap can replace larger volumes, it usually requires a position change with increased operative time, patient morbidity, and longer recovery while also exhausting a major reconstructive modality. In an effort to avoid this increased operative complexity, we have found that combining a local chest wall perforator flap and bioabsorbable implant, which has been previously shown to be safe and effective in reconstructing partial mastectomy defects, allows for a simpler VR strategy in patients who might otherwise require a more extensive thoracodorsal artery-based flap surgery or a mastectomy. Here, we present 10 cases where we combined flaps based off the lateral, anterior or medial intercostal artery perforators or lateral thoracic artery perforator with a bioabsorbable implant to successfully perform oncoplastic breast conservation in patients who might otherwise be marginal candidates for VR using a local chest wall perforator flap.